THE EFFECT OF PROBLEM BASED LEARNING MODEL THROUGH HOME VISITS AND LEARNING MOTIVATION ON Pipkin LEARNING OUTCOMES OF CLASS IV STUDENTS OF UPT SPF SDN 106828 SUMBERJO - Fadhlin Ade Candra Ade Candra; Deny Setiawan; Anita Yus (SENSEI RESEARCH CENTER, 2022)
This study aims to determine (1) the learning outcomes of students' PPKn taught by the Problem Based Learning model through home visits are higher than the PPKn learning outcomes of students taught by the Problem Based Learning model through Google Classroom; (2) PPKn learning outcomes of students who have high learning motivation are higher than students who have low learning motivation; (3) The interaction between the Problem Based Learning model through home visits and learning motivation on the learning outcomes of fourth grade PPKn at UPT SPF SDN 106828 Sumberjo. This research is in the form of a quasi-experimental design with a 2 x 2 factorial design. The population of this research is all fourth-grade students of UPT SPF SDN 106828, which are 2 classes with a total of 54 students. The sample selection was taken by using a total sampling technique, namely from the two classes as a whole set as a sample. Thus, the sample was determined, namely class IVA as group A and class IVB as group B. Class determination for the application of the learning model was determined by group A consisting of 27 students for classes taught using the Problem Based Learning model through home visits, and group B consisting of 27 students for classes taught using the Problem Based Learning model through google classroom. The research instrument used a multiple-choice learning outcome test with 25 questions and a student learning motivation instrument in the form of a questionnaire consisting of 40 items that were declared valid and reliable. Data analysis using two-way Anova. The results showed that (1) the learning outcomes of PPKn Education students who were taught using the Problem Based Learning model through home visits were higher than the Problem Based Learning model through the Google Classroom; (2) PPKn learning outcomes of students who have high learning motivation are higher than students who have low learning motivation; (3) There is an interaction between the learning model and learning motivation in influencing student PPKn learning outcomes.